A comparison of postprocedural anticoagulation in high‐risk patients undergoing WATCHMAN device implantation. Issue 10 (17th September 2019) - Cohen, Joshua A.; Heist, E. Kevin; Galvin, Jennifer; Lee, Hang; Johnson, Matthew; Fitzsimons, Michael; Slattery, Kathryn; Ghoshhajra, Brian; Sakhuja, Rahul; Ha, Grace; Forsch, Margaux; Shi, Linsheng; et al.
Abstract: Background: Left atrial appendage closure (LAAC) is an alternative to long‐term anticoagulation for thromboembolic protection in patients with atrial fibrillation (AF) and high bleeding risk. Short‐term Warfarin use following LAAC is well‐studied, while data pertaining to novel oral anticoagulant (NOAC) use in this setting is less robust. Specifically, data regarding the safety and efficacy of postprocedural NOAC use in high‐risk patients is lacking. Objective: To compare the safety and efficacy of Warfarin and NOAC use in a high‐risk patient population undergoing LAAC with the WATCHMAN device. Methods: From November 2015 to October 2017, 97 patients underwent LAAC with the WATCHMAN device. All patients were discussed at a multidisciplinary meeting prior to device implantation. Longitudinal data were collected and analyzed for a composite endpoint of stroke and death at 8 months, and major bleeding at 3 and 6 months. Results: Among the 90 patients included in the safety and efficacy analysis, 43 were prescribed Warfarin and 47 were prescribed NOACs. Baseline characteristics were comparable between study groups. There were no procedural complications and no significant differences in the incidence of death and stroke at 8 months or major bleeding at 3 and 6 months. Conclusion: For patients with AF at high risk of both thromboembolic and hemorrhagic events, NOACs as compared to Warfarin, seem to be safe and effective for short‐term anticoagulation following LAAC with the WATCHMAN device. Further validation in large randomized controlled trials is required.